Treatment outcome comparisons of first‐line targeted therapy in patients with KRAS wild‐type metastatic colorectal cancer: A nationwide database study - Liang, Yi‐Hsin; Chen, Kuo‐Hsing; Shao, Yu‐Yun (Cancer medicine (Malden, MA), 2023)
Background The first‐line systemic therapy for metastatic colorectal cancer (mCRC) is a combination of one targeted therapy agent and a chemotherapy doublet. Whether bevacizumab or anti‐epidermal growth factor receptor (anti‐EGFR) monoclonal antibody (mAb) is the more effective addition to a chemotherapy doublet as the first‐line treatment for inoperable KRAS wild‐type mCRC remains controversial in prior clinical trials. Moreover, the association between the sidedness of primary tumors and the efficacy of anti‐EGFR mAb needs to be addressed. Methods We established a cohort of patients with KRAS wild‐type mCRC who were treated with first‐line targeted therapy plus doublet chemotherapy between 2013 and 2018 using Taiwan's National Health Insurance Research Database. Secondary surgery was defined as either resection of primary tumors, liver metastases, lung metastases, or radiofrequency ablation. Results A total of 6482 patients were included; bevacizumab and anti‐EGFR mAb were the first‐line targeted therapies in 3334 (51.4%) and 3148 (48.6%) patients, respectively. Compared with those who received bevacizumab, patients who received anti‐EGFR mAb exhibited significantly longer overall survival (OS; median, 23.1 vs. 20.2 months, p = 0.012) and time to treatment failure (TTF; median, 11.3 vs. 10 months, p < 0.001). Among left‐sided primary tumors, the OS and TTF benefits of anti‐EGFR mAb remained. Among right‐sided primary tumors, the OS and TTF were similar regardless of the type of targeted therapy. In multivariate analyses, first‐line anti‐EGFR mAb therapy remained an independent predictor of longer OS and TTF for left‐sided primary tumors. Patients who received anti‐EGFR mAb were more likely to receive secondary surgery (29.6% vs. 22.6%, p < 0.0001) than patients who received bevacizumab. Conclusion For patients who received first‐line doublet chemotherapy for KRAS wild‐type mCRC, adding anti‐EGFR mAb was associated with significantly longer OS and TTF, especially for left‐sided primary tumors. Anti‐EGFR mAb was associated with significantly longer OS and TTF than the addition of bevacizumab.